2021
DOI: 10.1021/acs.energyfuels.1c01895
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review of Current Combustion Research Progress of Biodiesel and Model Compounds for Gas Turbine Application

Abstract: Biodiesel is one of the most promising low-carbon fuels and has been applied in internal combustion engines. In recent years, there have been emerging interests in the application of biodiesel in gas turbines, accompanied by the growing need for carbon reduction in the gas turbine industry. This mini review focuses on the fundamental combustion research of biodiesel and its model compounds, as well as its current application in gas turbines, mainly in the last 15 years. As for fundamental combustion research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…It is worth mentioning that this excellent review on moderate or intense low-oxygen diluted (MILD) combustion was selected by ACS editors to be featured as an ACS Editors' Choice. Liu et al 6 reported on the recent progress in using blends of fatty acid methyl esters and hydrocarbon fuels in gas turbines. Singh et al 7 discussed dual-fuel combustion engines, which can run on biodiesel and gas from biomass gasification, with the latter also called producer gas.…”
Section: ■ Review Papersmentioning
confidence: 99%
“…It is worth mentioning that this excellent review on moderate or intense low-oxygen diluted (MILD) combustion was selected by ACS editors to be featured as an ACS Editors' Choice. Liu et al 6 reported on the recent progress in using blends of fatty acid methyl esters and hydrocarbon fuels in gas turbines. Singh et al 7 discussed dual-fuel combustion engines, which can run on biodiesel and gas from biomass gasification, with the latter also called producer gas.…”
Section: ■ Review Papersmentioning
confidence: 99%
“…Petroleum-based fuel is the main motivation for developing countries around the world, including industry, transport facilities, and agricultural activities. Contrarily, petroleum-based fuel, as the main energy source, is unsustainability expected and its depletion is the fate. , The main characteristics of fuel extracted from fossil fuels have wide availability, efficient combusting ability, and high produced calorific value . The International Energy Agency estimates the growth of energy consumption from sustainable resources up to 53% by 2030 .…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear waste stored in underground tanks can also produce flammable mixtures . In addition, the introduction of renewable fuels into the energy matrix leads us to consider fuel mixtures involving gaseous fuels such as hydrogen and ammonia, and also liquid fuels involving blends of biodiesel and ethanol, , among others. In either case, a flammable mixture could form and FLs must be known for safe operation.…”
Section: Introductionmentioning
confidence: 99%